The Effect of Articulate Storyline 3-Based Physics Media on Students’ Interest and Learning Outcomes - Neta Dwi Wulandari; Alex Harijanto; Firdha Kusuma Ayu Anggraeni (Universitas Lambung Mangkurat, 2025)
One of the main factors in low learning outcomes for students occurs due to students' lack of interest in learning. This allows teachers to compete in creating interactive learning media so that students' interest in learning can be increased. So, the aims of this research are 1) to describe the effect of physics learning media based on Articulate Storyline 3 on high school students' interest in learning about Forces and Newton's Laws, and 2) to describe the effect of physics learning media based on Articulate Storyline 3 on the learning outcomes of high school students on Forces and Newton's Laws. The type and design of this research are true, with a quantitative approach and posttest-only control design. The results obtained in this research with the help of the SPSS 25 program, for student interest data using the Independent Sample T-Test, obtained a Sig value. (2-tailed) 0.001. Meanwhile, the student learning outcomes data obtained using the Mann-Whitney U-test obtained a Sig value. (2-tailed) 0.011. So the conclusion drawn based on the results obtained is that Articulate Storyline 3-based media has a good influence on students' interest in learning and their learning outcomes for high school students on Force and Newton's Laws.